Transcatheter mitral valve repair for the treatment of severe mitral regurgitation and exertional pre-syncope in a patient with non-obstructive hypertrophic cardiomyopathy: a case report. Issue 1 (17th November 2021) - Lucarelli, Katya; Troisi, Federica; Scarcia, Maria; Grimaldi, Massimo
Abstract: Background: Hypertrophic cardiomyopathy (HCM) has a complex pathophysiology and heterogeneous phenotypic expression. In obstructive HCM with significant mitral regurgitation (MR), MitraClip device implantation reduces MR severity and symptoms. There are no data regarding MitraClip implantation in patients with non-obstructive HCM and significant MR. Case summary: A 78-year-old woman with non-obstructive HCM and significant functional MR (3+) was admitted to our centre for dyspnoea and episodes of pre-syncope under light stress. Transthoracic and transoesophageal echocardiography showed a normal left ventricular ejection fraction and normal right heart pressures, an inverted mitral filling pattern, and a central prevalent jet (A2-P2 origin) of MR. Exercise echocardiography performed to verify exercise tolerance was interrupted at the 50-W stage due to severe hypotension and pre-syncope. After transcatheter edge-to-edge repair using the MitraClip system, the patient exhibited a reduction in MR Grade from 3+ to 1+. Follow-up up to 1-year post-procedure revealed noticeable improvements in exercise tolerance and symptoms. There were no further episodes of pre-syncope. Discussion: In non-obstructive HCM, the pathophysiological role of MR in symptom generation is unknown. In this patient, we speculated that significant MR contributed to the mechanisms responsible for severe hypotension and pre-syncope during exercise. A reduction in MR after MitraClip implantation was associated with symptomatic improvements. Our findings further highlight the potential utility of the exercise stress test in therapeutic decision-making for patients with non-obstructive HCM and MR.